The Legitimacy of Fractions in the People's Representative Council: Constitutional Criticism and Reconstruction of the Representative System from the Perspective of People's Sovereignty - Saor Siagian; John Pieris; Mompang L Panggabean; Aartje Tehupeiory (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
The existence of factions in the House of Representatives is an important element in the institutional practice of parliament in Indonesia. Factions function as a means of political coordination for members of the House of Representatives who come from the same political party in carrying out legislative, oversight, and budgeting functions. This study aims to analyze the position of factions in the Indonesian constitutional system and assess the institutional legitimacy of factions from the perspective of the principle of people’s sovereignty. This research uses a normative legal research method with legislative, conceptual, and comparative approaches. The results of the study show that factions are not explicitly regulated in the 1945 Constitution of the Republic of Indonesia but constitute an institutional construction established through laws and regulations governing the organization of the House of Representatives. The dominance of factions in parliamentary institutional practice has the potential to shift the representative function of the House of Representatives from representation of the people to representation of political parties. Therefore, it is necessary to reconstruct the position of factions in the Indonesian constitutional system to ensure a balance between the role of political parties and the principle of people’s sovereignty. From a more progressive perspective, this research also opens discursive space regarding the possibility of a parliamentary model that provides greater room for the independence of legislative members, including the idea of a parliament without factions as a conceptual alternative within a representative democratic system.